2017
DOI: 10.22610/jebs.v9i1.1572
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Enhanced Knowledge Management Framework for Retaining Research Knowledge among University Academics

Abstract: Given the challenge of retaining the research knowledge of an aging, experienced professoriate at South African Universities of Technology, institutions with a nascent tradition of scholarly research, this paper explores the feasibility of a technology-enhanced knowledge management framework for generating, sharing and retaining tacit research knowledge to leverage research outputs at the Central University of Technology (CUT), Free State, South Africa. Since digital trails of established-novice researcher int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The results also successfully justified the gap in the previous study (Bolander et al, 2017;Erasmus et al, 2017;Farooq et al, 2017;Maghdomi and Keikha, 2017;Miiro and Otham, 2018;Mohammed, 2018;Mohammed et al, 2020) by showing the significant relationship between talent management, knowledge management, university transformation, academic climate, and higher performance in education. Hazelkorn (2017), Masa'deh et al (2017, Rambe and Mbeo (2017), Paisey and Paisey (2018), and Karim and Majid (2019) observed the importance of managing talent and knowledge in enhancing higher education performance in the modern globalization era. The study indicated that skills and knowledge management are significant factors in achieving higher education performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results also successfully justified the gap in the previous study (Bolander et al, 2017;Erasmus et al, 2017;Farooq et al, 2017;Maghdomi and Keikha, 2017;Miiro and Otham, 2018;Mohammed, 2018;Mohammed et al, 2020) by showing the significant relationship between talent management, knowledge management, university transformation, academic climate, and higher performance in education. Hazelkorn (2017), Masa'deh et al (2017, Rambe and Mbeo (2017), Paisey and Paisey (2018), and Karim and Majid (2019) observed the importance of managing talent and knowledge in enhancing higher education performance in the modern globalization era. The study indicated that skills and knowledge management are significant factors in achieving higher education performance.…”
Section: Discussionmentioning
confidence: 99%
“…By utilizing organizational strategies with highly skilled employees, the talent management process is crucial to higher education institutions' long-term growth and success as an industry (Ming et al, 2016). Knowledge management is viewed as an integrated approach allowing organizations to meet the demands to increase competitiveness (Oktavia et al, 2017), which further results in high-quality educational outputs (Rambe and Mbeo, 2017). Therefore, a combination of talent and knowledge management helps transform and achieve improved academic performance and competitiveness (Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, several technological tools and elements are currently used, such as the Internet itself, data mining, big data and cloud computing, the Internet of things, and artificial intelligence, which have revolutionized the way information and knowledge are handled, passed on, and managed (Khan and Vorley, 2017;Oliva and Kotabe, 2019;Uden and He, 2017). Studies point to the existing relationship between the use of technologies (mainly information technologies) and knowledge management (Mao et al, 2016;Rambe and Mbeo, 2017;Oliva, 2014;Jarrahi et al, 2022;Mohiuddin et al, 2022). This allows for the elaboration of the following research hypothesis: H5.…”
Section: Knowledge Management Driversmentioning
confidence: 99%
“…In addition, strategically attracting, developing and retaining talent is key to the university's growth and success (Bradley, 2016). One of the benefits of implementing knowledge management in universities is in creating research and quality educational outcomes as part of knowledge management (Rambe & Mbeo, 2017). Implementing knowledge management is very important for universities to be successful and develop (Shams & Belyaeva, 2019).…”
Section: Talent Managementmentioning
confidence: 99%